2022
DOI: 10.1093/nar/gkac265
|View full text |Cite
|
Sign up to set email alerts
|

Active endogenous retroviral elements in human pluripotent stem cells play a role in regulating host gene expression

Abstract: Human endogenous retroviruses, also called LTR elements, can be bound by transcription factors and marked by different histone modifications in different biological contexts. Recently, individual LTR or certain subclasses of LTRs such as LTR7/HERVH and LTR5_Hs/HERVK families have been identified as cis-regulatory elements. However, there are still many LTR elements with unknown functions. Here, we dissected the landscape of histone modifications and regulatory map of LTRs by integrating 98 ChIP-seq data in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 78 publications
3
9
0
Order By: Relevance
“…7a, 7b ). This observation is consistent with the notion that the LTR7 can act as hESC enhancers to control the expression of distal human genes 43, 79 . By contrast, these human genes regulated by distal LTR7s are less likely to be affected by shRNA-mediated HERV-H knock-down.…”
Section: Discussionsupporting
confidence: 91%
“…7a, 7b ). This observation is consistent with the notion that the LTR7 can act as hESC enhancers to control the expression of distal human genes 43, 79 . By contrast, these human genes regulated by distal LTR7s are less likely to be affected by shRNA-mediated HERV-H knock-down.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we revealed that LTR5_Hs and LTR5_Pt carry a SOX2 binding motif (nucleotide positions 681–686), in addition to the previously identified POU5F1 motif (positions 692–698) ( Glinsky 2015 ; Grow et al 2015 ), which together form a POU5F1-SOX2 dual binding motif. Consistently, it was recently reported that the ChIP-seq data of both POU5F1 and SOX2 showed a peak in the region encompassing this motif in LTR5_Hs in human iPSCs ( Monde et al 2022 ) and human ESCs ( Zhang et al 2022 ). Owing to the sequence motif, retrotransposed LTR5_Hs and LTR5_Pt copies bind to POU5F1 and SOX2 and gain active histone marks, which underlie the species-specific active chromatin environment and activation of nearby genes in iPSCs.…”
Section: Discussionsupporting
confidence: 83%
“…On chromosomes 4, 5, 6, and 7, the actual number of identifications was lower than anticipated (Figure 1C). Notably, HML-9 provirus integration was not detected on chromosomes 1, 2B, 3,9,10,11,12,14,17,18,20,21,22, or X. For solo LTRs elements, the number of HML-9 solo LTRs on chromosomes 2A, 2B, 3, 7, 14, 21, X, and Y was higher than the expected number of integrations.…”
Section: Hml-9 Element Identification Localization and Distribution I...mentioning
confidence: 79%